Study of Jaw Bone Structure in Clinical Examination and Surgical Preparation for Dental Treatment: An Experimental Approach - Stupnytsky Ростислав; Stupnytsky Ілля-Олесь (Actual Dentistry, 2026)
Background. Studying the structure of the jaw bones during the surgical preparation phase is critical for minimizing risks and ensuring successful dental treatment. In turn, examining this structure during the assessment and preparation stages for surgical dental treatment in animal models represents a fundamental milestone for developing novel methods of implantation, bone grafting, and regenerative medicine. Objective. Based on experimental data, to develop a comprehensive set of preventive measures to avoid bone tissue atrophy within the extracted tooth socket by designing, applying, and implementing new techniques for the surgical preparation of the prosthetic bed tissues using autoplastic materials. Materials and Methods. During the experimental study on a domestic Large White pig model, clinical scenarios routinely faced by oral surgeons were replicated: modeling atrophy (tooth extraction followed by waiting for natural bone resorption); creating critical-size defects (forming bone cavities incapable of self-healing without the application of osteoplastic materials); and bone grafting (filling the defects with autologous bone, allomaterials, or xenografts). The experiments were conducted in strict compliance with bioethical norms. Results. It was established that revascularization occurred more intensively when utilizing the developed dental autograft. New blood vessels formed faster and in greater numbers, with osteogenesis elements developing around them. The proposed complex of preventive measures slows down resorption processes: vertical and horizontal bone loss in the surgical intervention area decreased compared to the control group (without augmentation). Autoplastic materials provided optimal bone regeneration due to the preservation of osteogenic potential and the absence of immunological rejection. Conclusions. The application of original augmentation techniques involving dental autografts optimizes the surgical preparation of prosthetic bed tissues and prevents the progression of post-extraction bone tissue atrophy of the alveolar part of the jaw.